Day Care Coronary Angiogram in Bangladesh- Our Experience with 100 cases - Momen, Abdul; Ali, Md Zulfikar; Rahman, Ashraf Ur; Huda, Reaz Mahmud; Nurunnabi, ABM; Haque, Md Monsurul; Alam, Iftequar; Sarker, Shudhakor; Ali, Mohammad; Alam, Md Abul; Sayami, Lima Asrin; Hashem, Sabina; et al. (Cardiovascular Journal, 2019)
Background: In conventional coronary angiography (CAG) by transfemoral approach patients usually need to stay at least one night in hospital. CAG by transradial approach gives the opportunity for same day hospital discharge. The objective of this study was to assess the safety and feasibly of day case CAG in Bangladesh. Methods: This is a single operator observational study where patients admitted for CAG through transradial (conventional and distal radial) approach were included. Patients were admitted at least 2 hours before the procedure. Hemostasis was done with manual compression followed by tight gauge-rolled bandage. Predischarge criteria had been set and applied to all patients. An emergency telephone number was given to the patient and they were contacted on the next day over telephone. Results: 30 (30%) female and 70 (70%) male were included with mean age 53±9SD years. Patients were discharged from the hospital on an average after 3.3±1.1 hours of the procedure. Only 4(4%) patients contacted to the emergency number. No bleeding complication was noted and 16(16%) patients complained about of some puncture site pain. Radial artery patency was was maintained in 96% of the patient on subsequent follow up. Conclusion: Same day hospital discharge is a feasible and safe alternative with similar radial artery patency rate. It will reduce the hospital cost and bed occupancy rate in a busy center in Bangladesh. Cardiovasc. j. 2019; 11(2): 152-158